A review of energy storage technologies in hydraulic wind turbines. (15th July 2022) - Ai, Chao; Zhang, Lin; Gao, Wei; Yang, Guisheng; Wu, Die; Chen, Lijuan; Chen, Wenting; Plummer, Andrew
Highlights: This paper summarizes the principles of storage and conversion of several kinds of energy in hydraulic wind turbines after the addition of hydraulic accumulators, compressed air energy storage, pumped hydroelectric storage technologies. This paper discusses the functions of the energy storage system in terms of the stabilizing speed, optimal power tracking and power smoothing when generating power from hydraulic wind turbines. In this paper, the development prospect and potential application of energy storage device in hydraulic wind turbines are predicted. Abstract: With the intensification of energy shortages and environmental pollution, new energy sources represented by wind and solar energy have received global attention. Although the proposal of hydraulic wind turbines effectively solves the problems of traditional wind turbine transmission impact and complicated installation and maintenance, further exploration is needed on how to solve the randomness and intermittency of wind. The introduction of energy storage technology into wind power provides a way to solve this problem. This article mainly reviews the energy storage technology used in hydraulic wind power and summarizes the energy transmission and reuse principles of hydraulic accumulators, compressed air energy storage and flywheel energy storage technologies, combined with hydraulic wind turbines. It also discusses the functions of the energy storage system in terms of the stabilizing speed, optimal power tracking, power smoothing, and power system frequency modulation when generating power from hydraulic wind turbines. Finally, the development and potential application of energy storage technology in hydraulic wind turbines in the future are predicted.